2016
DOI: 10.14814/phy2.12977
|View full text |Cite
|
Sign up to set email alerts
|

Plasma acylcarnitine profiling indicates increased fatty acid oxidation relative to tricarboxylic acid cycle capacity in young, healthy low birth weight men

Abstract: We hypothesized that an increased, incomplete fatty acid beta‐oxidation in mitochondria could be part of the metabolic events leading to insulin resistance and thereby an increased type 2 diabetes risk in low birth weight (LBW) compared with normal birth weight (NBW) individuals. Therefore, we measured fasting plasma levels of 45 acylcarnitine species in 18 LBW and 25 NBW men after an isocaloric control diet and a 5‐day high‐fat, high‐calorie diet. We demonstrated that LBW men had higher C2 and C4‐OH levels af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 59 publications
(153 reference statements)
8
31
0
Order By: Relevance
“…Taken together, we proposed that the acetyl‐CoA generation from in particular the increased fatty acid oxidation exceeds its oxidation in the TCA cycle in LBW individuals (Ribel‐Madsen et al. ), possibly due to a depletion of TCA cycle intermediates. In the state of a high intracellular acetyl‐CoA concentration, as seems to be the case in LBW individuals (Ribel‐Madsen et al.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Taken together, we proposed that the acetyl‐CoA generation from in particular the increased fatty acid oxidation exceeds its oxidation in the TCA cycle in LBW individuals (Ribel‐Madsen et al. ), possibly due to a depletion of TCA cycle intermediates. In the state of a high intracellular acetyl‐CoA concentration, as seems to be the case in LBW individuals (Ribel‐Madsen et al.…”
Section: Discussionmentioning
confidence: 74%
“…Previously, we have shown that LBW men have a higher plasma acetylcarnitine level after the control diet and a tendency to this after the high‐fat, high‐calorie diet compared with NBW men (Ribel‐Madsen et al. ), and in addition, an increased fatty acid oxidation and a decreased glucose oxidation at night during intake of both diets (Brons et al. , ).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations